Evaluation instruments for public health policies for elderly care: a scoping review protocol - Thaiza Teixeira Xavier Nobre; Margareth Santos de Amorim; Kleyton Santos de Medeiros; Clarissa Terenzi Seixas (BMJ Open)
Introduction The global phenomenon of population ageing is expanding rapidly, with WHO projecting that the number of individuals aged 60 and over will reach 2.1 billion by 2050, a significant rise from 900 million in 2015. This pronounced growth poses substantial challenges to healthcare systems globally, necessitating the development of effective public policies to ensure adequate access to healthcare services for the elderly demographic. In this context, this scoping review aims to identify and analyse theoretical and logical models, as well as evaluation instruments, of public policies directed at elderly healthcare.Methods and analysis This scoping review protocol is developed in accordance with the Joanna Briggs Institute manual and guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews. Article searches will be conducted in the following databases: Embase, Medline/PubMed, Scopus, Web of Science, Cumulative Index to Nursing and Allied Health Literature, Latin American and Caribbean Literature in Health Sciences and Science Direct. Additionally, searches will be performed on Google Scholar and in the grey literature (www.opengrey.eu). The search strategy will be conducted in January 2025, without language restriction for identifying texts. A descriptive analysis of the mapped studies will be conducted, categorising them by analysis categories. The results will be presented through a narrative summary of the findings to examine how they correlate with the review’s objective and research question.Ethics and dissemination This study does not require ethical review due to its nature. The results will be submitted for publication in a peer-reviewed journal and presented at a scientific conference.Trial registration number Open Science Framework: https://doi.org/10.17605/OSF.IO/AV4WH.